2020
DOI: 10.1097/ta.0000000000002965
|View full text |Cite
|
Sign up to set email alerts
|

Equity on the frontlines of trauma surgery: An #EAST4ALL roundtable

Abstract: BACKGROUND Inequity exists in surgical training and the workplace. The Eastern Association for the Surgery of Trauma (EAST) Equity, Quality, and Inclusion in Trauma Surgery Ad Hoc Task Force (EAST4ALL) sought to raise awareness and provide resources to combat these inequities. METHODS A study was conducted of EAST members to ascertain areas of inequity and lack of inclusion. Specific problems and barriers were identified that hindered inclusion. Toolkit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The perceived impact on patient care highlights the need for trauma teams and their institutions to not only recognize bias but also take actionable steps to mitigate it. In 2021, the #EAST4ALL roundtable found that the best ways to take action include “recognizing our own implicit bias, acting positively as an ally…, raising awareness of cultural competency, and ensuring institutional policies are inclusive 32 http://implicit.harvard.edu) could help team members identify these unconscious thoughts that may influence communication in the trauma bay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived impact on patient care highlights the need for trauma teams and their institutions to not only recognize bias but also take actionable steps to mitigate it. In 2021, the #EAST4ALL roundtable found that the best ways to take action include “recognizing our own implicit bias, acting positively as an ally…, raising awareness of cultural competency, and ensuring institutional policies are inclusive 32 http://implicit.harvard.edu) could help team members identify these unconscious thoughts that may influence communication in the trauma bay.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the #EAST4ALL roundtable found that the best ways to take action include "recognizing our own implicit bias, acting positively as an ally…, raising awareness of cultural competency, and ensuring institutional policies are inclusive. 32 " Institutional requirements for employees to take their own implicit bias association test (http://implicit.harvard.edu) could help team members identify these unconscious thoughts that may influence communication in the trauma bay. After a foundation of identifying these biases exist, institutional education and support using an Implicit Bias Toolkit, like the one provided by the National Association of Student Financial Aid Administrators (https://www.nasfaa.…”
Section: Femalementioning
confidence: 99%
“…Women Surgeons 31 and Eastern Associations for the Surgeon of Trauma, 32 play an instrumental role in raising awareness and advocacy. These efforts should be unified to attain the desired positive impact.…”
Section: Open Accessmentioning
confidence: 99%
“…12 This survey sought to characterize the demographics of EAST membership, their association with academia, role in EAST, and what types of discrimination they face in their daily practice. 13,14 The purpose of this study was to provide a current assessment of how women and SOC were represented within EAST and compare this with available organizational leadership data. We hypothesized that women and SOC are underrepresented as EAST members and in organizational leadership roles.…”
mentioning
confidence: 99%